Risk‐Taking Facilitates Implicit Learning in Young Adults - Amanda Cremone‐Caira; Melissa A. St. Hilaire (Brain and Behavior)
ABSTRACT Introduction Risk‐taking is associated with dynamic outcomes, including psychopathology and types of learning related to adaptive behaviors. The goal of the current study was to (1) evaluate risk‐related learning in a sample of neurotypical young adults and (2) determine how risk‐taking related to motivation and emotional processing (as measured by BIS/BAS Scales). Methods Fifty‐eight young adults (Mage = 19.66 years, SD = 1.43 years; 74% female) completed the Balloon Emotional Learning Task (BELT) and the BIS/BAS to measure risk‐taking tendencies and motivation and emotional processing, respectively. Results Generalized linear mixed models indicate that participants learned to make more advantageous decisions as they engaged in risk‐taking behaviors during the BELT. Risk‐taking outcomes were positively correlated with self‐report of participant's persistent pursuit of goals as measured by the BAS Drive Scale, although these findings were no longer significant after correcting for multiple comparisons. Conclusions Together, these results suggest that, in some contexts, risk‐taking may support learning and goal‐directed behaviors in young adults. These findings have notable implications in improving educational and professional outcomes.